Pengaruh Pendapatan, Jumlah Nasabah, Dan Suku Bunga Terhadap Penyaluran Kredit Pada Pt. Pegadaian (Persero) Cabang Semarang Di Masa Pandemi Covid 19 - Maharani, Safitri; Poerwati, Rr Tjahjaning (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to analyze the effect of income, number of customers, and interest rates on credit distribution of PT.  Pegadaian (Persero) Semarang branch in 2018-2020.  The sample of this study was determined by purposive sampling method based on the first criteria of PT.  Pegadaian (Persero) Semarang branch in 2018-2020, the two PT.  Pegadaian (Persero) Semarang branch with increased distribution in 2015-2019, and the three PT.  Pegadaian (Persero) Semarang branch which has the necessary data in full to support the research being carried out such as: Income, Number of Customers, Interest Rates, and also Credit Distribution data, so that a sample of 48 outlets of PT.  Pegadaian (Persero) Semarang branch.  This research uses multiple linear regression model.  The results of this study conclude that income has a significant effect on Credit Disbursement.  The number of customers has no significant effect on Credit Disbursement, and interest rates have a significant effect on Credit Disbursement.